Mysis segerstralei, an unexpected but important prey for resident Arctic charr (Salvelinus alpinus) in a Svalbard lake - Svenning, Martin; Skogstad, Ole Christiam; Skogstad, Øyvind; Borgstrøm, Reidar (Polar Biology, 2024)
Mysis segerstralei is distributed over a wide geographic area and in habitats with a variety of salinity conditions, including marine and brackish waters around Svalbard. The species has seldom been found in freshwater lakes, and the discovery of M. segerstralei in Lake Pulmankijärvi at the border between Northeastern Norway and Finland, may represent the single known freshwater occurrences in western Europe. Svalbard lake systems are characterized by very low water temperatures, long-term ice cover, and low levels of nutrients. Food is thus limited, and chironomids generally dominate the stomach contents in Arctic charr, the only freshwater fish species on Svalbard. Based on several surveys in more than 30 of Svalbard lakes over many decades, M. segerstralei has only been found as food for Arctic charr in Lake Vårfluesjøen. In a later fishery survey, we studied the diet of Arctic charr in this lake. The stomach contents from Arctic charr sampled in the profundal habitats were dominated by M. segerstralei, but the species was also among the most frequent prey items in the littoral and pelagic habitats. This unexpected occurrence of M. segerstralei demonstrates the high importance of mysids even in a low-productive, High Arctic lake. Glacial relicts · Mysis segerstralei · Arctic charr · Salvelinus alpinus · Svalbard freshwater lakes · High Arctic Mysis segerstralei, an unexpected but important prey for resident Arctic charr (Salvelinus alpinus) in a Svalbard lake publishedVersion